Real-time human detection for video surveillance - Kamru Zaman, Fadhlan H.; Shafie, Amir A.; Khalifa, Othman Omran (IIUM Press, 2011)
Recent research in computer vision has increasingly focused on building systems for observing humans and understanding their appearance, movements, and activities, providing advanced interfaces for interacting with humans, and creating realistic models of humans for various purposes (Ogale, 2006). For the last decades, video analysis and understanding has been one of the main active fields in computer vision and image analysis where applications relying on this field are various, like video surveillance, object tracking and traffic monitoring. (Allili et aI, 2007). The ability of computer vision to recognize human from the image and works similar to human eye has made computer vision to be used widely in various applications especially in video analysis